Peran Mindful Parenting Terhadap Parenting Stress Pada Ibu yang Bekerja - Srifianti, Srifianti; Kristiyani, Veronica; Lunanta, Lita Patricia; Hatta, Andi Rina (Esa Unggul University, 2022)
The increasing number of violence against children, which in February 2020 was reported to be 2,851, increased to 7,190 cases in December 2020. This shows that the psychological condition of parents can affect their behavior in parenting and greatly affect the development of children. Parents, especially working mothers, have challenges to carry out their role of caring for children while working. This will be a stressor for a mother as a parent who has a major role in raising her child. To reduce the stressful conditions experienced by parents in parenting, it is necessary to have training and awareness from within the parents. Awareness in parents can be trained and understood through parenting that is carried out with full awareness continuously called mindful parenting. The purpose of this study is to analyze the effect of mindful parenting on parenting stress. The population and sample in this study were parents, especially working mothers, amounting to 113 people. The measuring instrument used to measure mindful parenting is the Mindfulness in Parenting Scale (MIPQ) developed by McCaffrey, Reitman and Black (2017) with a reliability value of 0.865. Meanwhile, the measuring instrument for measuring parenting stress is the Parenting Stress Scale, a measuring instrument developed by Berry and Jones (1995) with a reliability value of 0.87. The research method used is the simple linear regression method, and the analytical test used is SPSS 25. The results showed that there was a significant negative effect between mindful parenting on parenting stress in working mothers.